Social, economic and environmental policy complementarity in the South African mining sector - Sophie Plagerson; Lauren Stuart (United Nations Research Institute for Social Development (UNRISD), 2018)
This paper considers the complementarity of social, economic and environmental policy in South Africa, using the mining sector as a case study. The mining sector has been chosen due to its unique position as a backbone of the South African economy, its historical significance and impact on social conditions, and its key role in shaping social policy. The paper considers policy complementarity as critical for social, economic and environmental development in order to achieve optimal redistributive outcomes, and develops an analytical framework for assessing policy complementarity through the dimensions of "autonomy", "alignment" and "adjustment". The paper assesses the policy complementarity of pre- and post-apartheid policy mandates; and the intersections between policy actors from the state, the mining industry, labour and civil society. This analysis finds that intersectoral policy connections are necessary, but not sufficient, for the achievement of optimal redistributive outcomes. While South Africa benefits from a robust intersectoral post-apartheid legislative and policy framework, and progress has been made in several areas, significant challenges remain as evidenced by the slow pace of legislative reform, institutionalized political corruption, low levels of trust between stakeholders, differing perspectives on the meaning of "transformation" and who is responsible for its attainment, and internal divisions in the labour sector. The paper concludes that three factors are of particular importance in promoting policy complementarity: the presence of multilateral platforms to accommodate dialogue and negotiation between stakeholders to develop the social pacts required for sustainable development; the retention of sectoral expertise within state structures to enable the effective intersectoral implementation of policy; and that policy be enshrined in legislation, protected and enforced by a strong court system.
Additional information: Prepared for the UNRISD project New Directions in Social Policy: Alternatives from and for the Global South
Keywords: 330